The effect of family counseling programs on prevention of psychological abuse of elderly women - Heravi Karimoi M; Jadid Milani M; Faghihzadeh S (Tehran University of Medical Sciences, 2005)
Introduction: Attention to psychological abuse of old women as a vulnerable group and its complications are important issues. We performed this study to determine the effect of family counseling program on prevention of psychological abuse of elderly women. Methods and Materials: This is a semi-experimental study. We selected 30 old women referring to clinics of an educational hospital in Tehran by simple randomization. Data collecting instruments included demographic sheets about old person and family members and a questionnaire about psychological abuse, which were completed by interview. An observational checklist about behavioral symptoms was completed at 3 interview sessions by family and old person at home. Then 6 counseling sessions were established. Duration of every session was 1:30 up to 2 hours. After two months and in the last three sessions, final evaluation was conducted by again completing data collecting instruments. Results: study results showed that 90% of abusers were woman and family dysfunction was the reason of abuse in 43.3% of cases. Mean score of psychological abuse showed a significant decrease after counseling, using dependent t-test and Wilcoxon test (p<0.001). Also, mean score of behavioral symptoms of abuse showed a statistically significant decrease after counseling, using dependent t-test and Wilcoxon (p<0.001). Pearson correlation coefficient (r=0.90) showed that there was a significant correlation between psychological abuse and behavioral symptoms. Conclusion: Regarding positive effect of family counselling programs on reduction of psychological abuse of old women, it is suggested that effect of family counseling programs in reduction of other types of abuse be determined.